ERCP performed and described by surgical endoscopists - Ethan Craig; Carolina Jimenez; Robert Bowles; Jose Martinez; Robert Cubas (Revista de la Facultad de Ciencias Médicas de Córdoba, 2025)
Endoscopic retrograde cholangiopancreatography (ERCP) is an advanced endoscopic procedure that uses fluoroscopy to diagnose and treat diseases within the biliopancreatic system. The first ERCP was performed by surgeons in 1968 at George Washington University. While ERCP is most commonly performed by gastroenterologists, surgeons with training in advanced gastrointestinal endoscopy have demonstrated similar success rates and outcomes despite differing training pathways. The purpose of this review is to highlight basic tenants of ERCP and describe how ERCP is performed in our practice.